Adaptive reuse of heritage building - Basha, Brunilda; Abdullah, Fadzidah; Soomro, Ali Raza (IIUM Press, International Islamic University Malaysia, 2017)
Historic buildings maintain the local characteristics and preserve the culture and history of a country. This historical and cultural significances as a legacy can be passed to next generation by conserving the historical buildings. Nowadays in the process of conservation, Adaptive Reuse Practice has been necessary, especially when historical buildings are no longer functioning its original purpose. In the pursuit of the sustainable development, social sustainability has been the new parameter to investigate the viability of adaptive reuse. There are not enough studies held to explore the social parameter. In this regard an attempt has been made to investigate the viability of adaptive reuse and its social sustainability. Asia Heritage Row located in Doraisami Street and Jalan Yap Ah Shak, Kuala Lumpur, is used for the hypobook testing. The purpose of this book is to assess re-adaptive building impact to the social life of the users and their satisfaction after application of adaptive reuse and to evaluate the contribution of Asia Heritage Row after application of adaptive reuse towards cultural and aesthetical heritage values. The data is mainly collected from literature review, case study and questionnaires distributed to the end users of the Asia Heritage Row. The data is analyzed by determining the statically reliable relationship between adaptive reuse and social sustainability parameters. The associations between variables are examined by correlation. The findings show that adaptive reuse of Asia Heritage Row building has a significant value both; culturally and socially. It preserves the heritage significances as a place of social interaction and ensures its sustainability. The book then provides recommendations to improve application of adaptive reuse to the heritage buildings for future reference.